SPECTROSCOPY AND PHOTOMETRY OF BE STAR MWC340 - Kurchakov, A. V.; Rspaev, F. K. (Одеські астрономічні публікації, 2007)
The spectroscopic and photometric observations of Be star MWC 340 made at Fesenkov Astrophysical institute during 2001-2006 are presented.